An Analytical Framework for Cross-Cultural Studies of Teaching - Daniel D. Pratt (Adult Education Research Conference, 1999)
Working cross-culturally, whether defined by discipline, institution, community, or nation-state, inherently means working outside the familiar. The aim of this paper is to present an analytical framework through which to explore and understand different conceptions of teaching. The framework consists of three analytical categories: epistemic beliefs, normative expectations, and pedagogical procedures.